Measurement of the Efficiency Level of Islamic Insurance Firms in Indonesia: DEA and SFA Analysis - Mirza Mayang Safitri; Ratna Sofiana; Hilmy Baroroh; Muhfiatun Muhfiatun (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to measure the efficiency level of Islamic insurance companies in Indonesia using DEA and SFA, with secondary data from 13 companies in the 2019-2023 period. DEA measures the relative technical efficiency of a company compared to other companies in the same group, while SFA measures efficiency by considering stochastic factors that can affect company performance. The results show that there is high variation in efficiency between companies in DEA, while SFA produces efficiency scores above 60%, tending to be higher than DEA. This research provides practical implications for Islamic insurance companies to improve efficiency through resource optimization, in order to get maximum output so that the efficiency level of Islamic insurance companies can increase.